2021
DOI: 10.48550/arxiv.2110.05953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex, Lorentzian, and Euclidean simplicial quantum gravity: numerical methods and physical prospects

Ding Jia

Abstract: Evaluating gravitational path integrals in the Lorentzian has been a longstanding challenge due to the numerical sign problem. We show that this challenge can be overcome in simplicial quantum gravity. By deforming the integration contour into the complex, the sign fluctuations can be suppressed, for instance using the holomorphic gradient flow algorithm. Working through simple models, we show that this algorithm enables efficient Monte Carlo simulations for Lorentzian simplicial quantum gravity.In order to al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…[24,25]. If the two points are on neighbouring hyperbolae, the angle is specified (in the convention of [25]) by a real part Re(ψ L± ) ∈ R and an imaginary contribution of either Im(ψ L+ ) = −π/2 (a choice advertised in [25]) or Im(ψ L− ) = +π/2 (which was used in [11]). As discussed in the introduction, the choice of sign determines which kind of causality violations are suppressed and which are enhanced.…”
Section: A On the Definition Of Angles In The Minkowskian Planementioning
confidence: 99%
See 2 more Smart Citations
“…[24,25]. If the two points are on neighbouring hyperbolae, the angle is specified (in the convention of [25]) by a real part Re(ψ L± ) ∈ R and an imaginary contribution of either Im(ψ L+ ) = −π/2 (a choice advertised in [25]) or Im(ψ L− ) = +π/2 (which was used in [11]). As discussed in the introduction, the choice of sign determines which kind of causality violations are suppressed and which are enhanced.…”
Section: A On the Definition Of Angles In The Minkowskian Planementioning
confidence: 99%
“…In particular, it can be shown that only Lefschetz thimbles for critical points whose anti-thimbles (defined by (4.15) but with +∞) cut the original integration domain, contribute. Since by construction Lefschetz thimbles have the property that the real part of the exponent decays as quickly as possible along them, while the imaginary part remains constant, integrals of the form ∼ e W along them can become absolutely convergent, ease oscillatory behaviour for numerical simulations and be subject to Monte-Carlo simulations [3,5,11].…”
Section: Deforming the Integration Contour To Approximate The Lefsche...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Lorentzian path integral is in particular important for quantum gravity [6][7][8][9][10][11]. Euclidean quantum gravity approaches use a formal Wick rotation, to justify a path integral based on the Euclidean gravity action, over Euclidean metrics.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently a proposal for simulating Lorentzian QRC models (precisely speaking, complex generalizations of QRC) by applying the "generalized thimble algorithm" has been proposed [24]. 3 An improvement in applying the Gaussian quadrature to theories with continuous variables is described in [29].…”
Section: Introductionmentioning
confidence: 99%